Effect of Cancer Related Fatigue tTo the Level of Independence of Cancer Patients and Caregiver Stress Level - Werdani, Yesiana Dwi Wahyu (Folia Medica Indonesiana, 2018)
Chemotherapy/radiation in cancer patients causes cancer-related fatigue (CRF). It affects the level of independence of patients' activity of daily living (ADL). Thus, the responsibility of caregivers will be higher and it impacts on caregiver stress level. The aim of this study was to prove the effects of CRF on independence level of cancer patients and caregivers' stress level. This study used analytical associative design. The population was cancer patients and caregivers in Yayasan Kanker Indonesia in East Java. The number of samples were 30 cancer patients and 30 caregivers, taken by total sampling method. The assessment was based on instrument brief fatigue questionnaire, activity of daily living based on Katz, and caregiver stress on self assessment questionnaire. The effects of CRF on the level of independence were indicated by p=0.000, and the levels of independence of the caregiver stress level were indicated by p=0.000. As a conclusion, the failure of muscle function due to CRF can affect the independence of patient's ADL fulfilling, so caregiver should take much time to treat patient and it affects on the increased stress level of caregiver.